Budaya Religius Sekolah Sebagai Upaya Membentuk Kecerdasan Emosional Siswa di UPT SMP Negeri 5 Medan - Nanda Arifa Albi (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2022)
Education in Indonesia today seems to be only oriented to cognitive intelligence. So many character degradation problems that arise. This is because education in Indonesia is still lacking in developing students' emotional intelligence. Realizing this reality, there needs to be a concrete and sustainable solution. In this case the school's religious culture can be used as a tool to realize the formation of student character. Therefore, the purpose of this study is to describe the form of school religious culture, and analyze the contribution of school religious culture to students' emotional intelligence. This research is a type of qualitative research. The results showed that the form of school religious culture at UPT SMP Negeri 5 Medan consisted of 2 implementations, namely a) daily activities such as prayer before and after lessons. b) weekly activities consisting of istighosah program, memorizing the Qur'an leading Asmaul Husna, and Friday alms. While the contribution of school religious culture as an effort to form students' emotional intelligence consists of a) istighosah can form emotional management, b) memorizing the Qur'an and leading Asmaul Husna readings can shape students' self-motivation, c) Friday alms can form student empathy and sincerity in giving alms, d) religious cultural activities as a whole are able to raise students' self-awareness.